1984
DOI: 10.1111/j.1540-8159.1984.tb04852.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive Evaluation of Ventricular Function and Volumes During Atrioventricular Sequential and Ventricular Pacing

Abstract: Thirteen patients who all had previously inserted temporary or permanent pacemakers (6, VVI; 7, A-V sequential) were studied by two-dimensional echocardiography and radionuclide gated blood pool ventriculography (RVG) for non-invasive evaluation of cardiac performance. Patients were paced in both the VVI mode and during sinus/atrial or A-V sequential pacing. Although there was no objective change of the ejection fraction during V-pacing and atrial/A-V sequential pacing or sinus rhythm, as has been previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Three pacing modes are used in pacemaker therapy for SSS patients (VVI, AAI, and DDD). Previous studies revealed VVI had less benefit compared with physiological pacing modes (AAI and DDD) 1–6 . However, the difference between AAI and DDD is still under discussion 15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three pacing modes are used in pacemaker therapy for SSS patients (VVI, AAI, and DDD). Previous studies revealed VVI had less benefit compared with physiological pacing modes (AAI and DDD) 1–6 . However, the difference between AAI and DDD is still under discussion 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Dual chamber pacing (DDD), single lead atrial pacing (AAI), and single lead ventricular pacing (VVI) are used for the treatment of sick sinus syndrome (SSS). Many reports showed that physiological pacing modes (DDD and AAI) were superior to VVI for the following reasons: cardiac output, 1–3 complications of atrial fibrillation, 4,5 thromboembolism, 4 heart failure, 4–6 survival rate, 4 and quality‐of‐life 5 . However, there are few reports comparing DDD with AAI 7–11 .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of LA con- tribution to LV performance during ventricular pacing was previously shown in dogs 8 and humans. 6,9,10 Padeletti et al 19 demonstrated that optimal AV delay was longer in patients with the atrial lead located in the RAA versus intraatrial septum. LV function was also related to ventricular pacing lead location in dogs 20 and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have evaluated the dependence of ventricular performance on AV coupling. [6][7][8][9][10] In addition, the increased clinical use of active-fixation atrial pacing leads has stimulated exploration of alternative atrial lead locations to prevent atrial arrhythmias. [11][12][13][14][15] The present investigation tested the hypothesis that atrial pacing lead location can change the dependence of left atrial (LA) and left ventricular (LV) hemodynamics on AV timing in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic benefits of dual chamber pacing including adaptation to sinus rhythm and maintenance of AV synchrony, [24][25][26][27][28] have been demonstrated by Doppler, 10,14,15,29,30 radionuclide, 31 and invasive 32 studies in patients with diverse underlying pathologies. 9,10,[33][34][35][36][37][38][39][40] Cardiac output may increase by nearly 30% in AV synchronous pacing compared to ventricular inhibited single chamber pacing.…”
Section: Discussionmentioning
confidence: 99%